Spark plasma sintering of Al2O3-filled preceramic paper for membrane supports; Materials Letters; Vol. 383 - Syrtanov M. S. Maksim Sergeevich; Zabanov Zh. G. Zhalsan Georgievich; Sedanova E. P. Elizaveta Pavlovna; Pushilina N. S. Natalia Sergeevna; Lomygin A. D. Anton Dmitrievich; Shichalin O. O. Oleg Olegovich; Kashkarov E. B. Egor Borisovich; Travitsky (Travitzky) N. Nakhum (2025, 2025)
Title screen